The Influence of Guided Inquiry Learning Models on Procedural Learning Outcomes of Junior High School Students - Janah, Nadya Miftaqul; Degeng, Made Duananda Kartika; Abidin, Zainul (Universitas Negeri Malang, 2024)
Learning outcomes in the procedural field of study are very much needed in learning because students are often confused in digesting the procedures explained, especially in complex science material. The aim of this research is to determine whether or not there is an influence of the guided inquiry learning model on the procedural learning outcomes of class VIII students at SMP Negeri 32 Surabaya. The material used by researchers in this research is the human circulatory system. This research is classified as quasi-experimental research using quantitative methods with a posttest control group design research design. The number of students in this study was 60 students who were divided into 2 groups. The average score for the experimental class was 84.70 and the control class was 76.77. Based on these results, after carrying out the Independent Sample t Test, it can be concluded that the results of this research indicate that there is an influence of the guided inquiry model on the procedural learning outcomes